Development of an Integrated E-Module on Religious Values in Human Digestive System Material for Grade VIII Junior High School/MTs - Nadya Afriani; Dini Afriansyah; Jhon Riswanda; Diah Putri Anggun (Bioedunis Journal, 2025)
This study is a Research and Development study, namely product development including validity and practicality tests. The ADDIE model consists of the stages of analysis, design, and development with details, one to one and small groups. Data collection was in the form of observation, interviews, and questionnaires. The results are as follows: media experts rated the product as 98% “highly valid,” subject matter experts rated it as 92% “highly valid,” language experts rated it as 80% “valid,” interpretation experts rated it as 77% “valid,” and religious values experts rated it as 98% “highly valid,” with an average validation score of 89% “highly valid” and suitable for use. The results of the practicality test from the educators were 97% “very practical,” one-to-one evaluation 89% “very practical,” and small group evaluation 88% “very practical,” with an average result of 91% categorized as “very practical” for application in the learning process.